(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
This research is set out to review of “optimum the water complex resources system by using dynamic programming DP and Discrete Differential Dynamic Programming DDDP, Beside a solution of formulated DP optimization model, the model of simulation was adopt for achieve the operation as close to optimum operation as possible, with the keep level of storage and releases within their targets”. In aiming at the optimal solution of the reservoir – operation problem, (DP) represents a numerical method which is used to determine the optimal sequential decisions, taking into consideration an effective constraints associated with problem. DDDP is the solution procedure of many problems which already formulated as dynamic – programming ones. It is reduce the memory requirements and save computational time. The Optimization model was applied for “two operations hypothetical represented by the cases of extreme, namely consecutive to the relatively of two wet years and two consecutive the relatively of dry years”. The data to the historical inflow for “(240) months are (from Oct. 1988 to Sep. 2005) was form to the data input to a model of optimization for found rule curves (lower, average and upper)”. A flooding state within Al_Edhaim Resevoir has been fully avoided. “The policy to the optimization of operation is shown a deficiency in satisfying downstream Al-Edhaim Dam demands”. “The optimization of the operation for two consecutive wet years would be full capable controlling expected floods, so as to the deficiency would be from 9.3–59.1 cumecs total of 34.2% of demand, then the optimization of the operation for two consecutive dry years would be from 11.8 – 81.2 cumecs total of 57.3 % of the whole demand".